Nilai dan Manfaat yang Terkandung dalam Silasa I - Mustafa Mustafa (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2015)
The purpose of this research is to express cultural values and advantages reflected in Silasa I (title of a book of Buginese ancestors’ moral advices). Originally, these advices were only spoken verbally by older people. The type of oral literature is stillalive among the Buginese community. The advices have been mostly inventoried. However, the studies on these advices in Silasa I have not been sufficiently done and met expectations of Buginese literature observers yet. The data of this research are collected through library research and field study. The results indicate that there arecultural values in Silasa; (1) honesty, (2) the nature of envy, bravery, cowardness, and(3) responsibility. While the advantages of Silasa serve as; (1) a reference of moral advices,(2) a philosophy of life, and (3) an interrelationship ties